(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Competition is a struggle between independent producers (enterprises) to produce goods on favorable terms and sell them at a good price, to strengthen their position in the economy as a whole. This article provides the necessary insights into competition and how to create pure competition between businesses.